253 COMPARISON OF HEME OXYGENASE ACTIVITY IN GUT-ASSOCIATED LYMPHOID TISSUES AND THE INTESTINE. Issue 1 (1st January 2007) - Burns-Guydish, S. M.; Wong, R. J.; Kalish, F.; Contag, C. H.; Stevenson, D. K.
Abstract : Heme oxygenase (HO) is the rate-limiting enzyme in the heme degradation pathway, which leads to the formation of equimolar amounts of carbon dioxide (CO), iron, and biliverdin. Biliverdin is quickly reduced to bilirubin by biliverdin reductase. These bioactive products of HO provide a potent cytoprotective effect through its antioxidant, antiapoptotic, and anti-inflammatory functions. Although HO is thought to be crucial for maintaining normal gastrointestinal (GI) function, the inducible HO-1 isozyme (which is up-regulated by endotoxin, heme, stress, etc.) may also have an important role in response to pathogens encountered in the GI tract. Previously, we have found that HO activity is significantly reduced in the jejunum of young compared with adult mice. Since neonates are acutely susceptible to GI infections, we hypothesized that HO (specifically HO-1) may be important in protection and in the response to infection. HO has been well characterized in the epithelium of the small intestine, but little is known about HO in the gut-associated lymphoid tissues (GALT), specifically the Peyer's patches (PP) and mesenteric lymph nodes (MLN). The GALT plays a major role in immune surveillance and may be key to the neonate's susceptibility to infection. Therefore, we sought to characterize total HO enzyme activity not only in the intestinal tissue but also in the GALT of adult mice. Total HO activity was determined in the following tissues: jejunum, jejunum-PP (jejunum with PP removed), PP, MLN, cecum, and colon by measurements of CO using gas chromatography. The jejunum-PP had significantly less activity (40.6 ± 22.6) than the jejunum with PP intact (113.3 ± 9.7). HO activity in the PP and MLN was 109 ± 33.8 and 95.8 ± 15.2, respectively, and was significantly greater (two- to threefold) than that in the jejunum-PP, cecum (48.2 ± 16.3), and colon (32.8 ± 6.6). In conclusion, we report for the first time the presence of HO activity in the PP and MLN of the GALT and that HO activity in these tissues is significantly greater than other intestinal tissues. We speculate that HO in the GALT may be important in protection and response to GI infections since its reduced expression in the intestine of young mice correlates with their increased susceptibility. This work was study was supported in part by National Institutes of Health grant #HL68703, the Mary L. Johnson Research Fund, and the Christopher Hess Research Fund.